2023
DOI: 10.3390/ani13061073
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cold Stress on Physiological, Endocrinological, Immunological, Metabolic, and Behavioral Changes of Beef Cattle at Different Stages of Growth

Abstract: The purpose of this study was to investigate the effect of cold stress (CS) on the physiological, blood, and behavioral parameters of beef cattle according to their growth stage. Twelve calves in the growing stages (220.4 ± 12.33 kg, male and non-castrated) and twelve steers in the early fattening stages (314.2 ± 18.44 kg) were used in this experiment. The animals were randomly distributed into three homogenized groups (four animals each) for 14 days, namely threshold, mild–moderate cold stress (MCS), and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Exposure to a cold climate could induce metabolic changes in beef cattle, leading to decreased growth performance and production efficiency [ 28 ]. Previous studies have defined mild, moderate, and severe cold stress temperatures for cattle as 0 to −6.7 °C, −7.2 to −13.9 °C, or <−13.9 °C, respectively [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to a cold climate could induce metabolic changes in beef cattle, leading to decreased growth performance and production efficiency [ 28 ]. Previous studies have defined mild, moderate, and severe cold stress temperatures for cattle as 0 to −6.7 °C, −7.2 to −13.9 °C, or <−13.9 °C, respectively [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the same animals showed behavioral alterations during cold periods, such as spending more time standing than lying down or eating. Similarly, in calves during the growing stage, Kim et al [55] found that, when compared to threshold values, calves exposed to extreme cold stress (−4.33 • C) significantly increased their cortisol concentrations (8.97 vs. 12.60 ng/mL, respectively), while a decrease in blood glucose was registered (71.00 vs. 61.75 mg/dL, respectively). This was also observed by Uetake et al [57], who determined that lactating dairy cows in cold-temperate climates had higher hair cortisol values (between 15 and 16 pg/mg of hair) than those located in warm-temperature regions (between 10 and 11 pg/mg).…”
Section: Hypothalamus and Central Thermal Modulationmentioning
confidence: 91%
“…Moreover, mild hypothermia (35 • C) in rats increases their plasma levels of corticosterone and thyrotropin-releasing hormone while their prolactin levels decrease [54]. Likewise, in cattle, exposure to mild/moderate (−1.05 • C) and extreme cold (−4.33 • C) resulted in increases in cortisol (7.00 ng/mL and 11.38 ng/mL, respectively) [55]. The hormonal response observed in hypothermic animals is greatly influenced by the hypothalamic-pituitary-adrenal (HPA) axis, which is triggered when the organism perceives alterations in homeostasis, including a decrease in their core temperature.…”
Section: Hypothalamus and Central Thermal Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In livestock tracking, animals are considered complex active systems mainly due to variability in actions and poses, as well as different sizes and sudden movements. Traditionally, monitoring animals in indoor barns has been possible through direct observation [ 6 ] or by using wireless wearable devices [ 7 ], such as neck collars, ear tags, and leg tags. An extensive literature has demonstrated the utility of these devices [ 8 ].…”
Section: Introductionmentioning
confidence: 99%